2007
DOI: 10.3141/2009-02
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movement Patterns for Novice Teen Drivers

Abstract: Attention to the road is essential to safe driving, but the development of appropriate eye glance scanning behaviors may require substantial driving experience. Novice teen drivers may focus almost exclusively on the road ahead rather than scanning the mirrors, and when performing secondary tasks, they may spend more time with eyes on the task than on the road. This paper examines the extent to which the scanning of novice teens improves with experience. For this study, 18 novice teen (younger than 17.5 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…However, most adults looked at the stop sign and displayed signs of indecision/late recognition. Previous research over the last 35 years and across several testing environments has consistently reported that adults scan more thoroughly and widely than novice teenagers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Notably, in the present research, only half of the teens looked at the stop sign in this scenario.…”
Section: Conclusion Hidden Stop-sign Scenariosupporting
confidence: 40%
See 1 more Smart Citation
“…However, most adults looked at the stop sign and displayed signs of indecision/late recognition. Previous research over the last 35 years and across several testing environments has consistently reported that adults scan more thoroughly and widely than novice teenagers (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Notably, in the present research, only half of the teens looked at the stop sign in this scenario.…”
Section: Conclusion Hidden Stop-sign Scenariosupporting
confidence: 40%
“…The early research of Mourant and Rockwell (12,13,14,15) was the first to reveal differences between novices and experienced drivers in terms of the visual acquisition process (scanning forward and to the mirrors) and the frequency of lane-line sampling while driving on the open road. Additional efforts have recently begun using a test-track to evaluate differences between adult and novice drivers (16,17,18,19), during which differences were found in terms of stopping behavior (at an intersection) and scanning behavior. For example, adults have been found to be more likely to stop at a changing traffic light than youth, and teens tend to have fewer mirror glances than adults.…”
Section: Introductionmentioning
confidence: 99%
“…Olsen et al (2007) found that 6 months of driving experience for novice drivers did not decrease their Eyes Off Road time (EOR) while performing secondary tasks in a test track study. If six months of driving experience do not decrease the EOR time, one can assume that the metric used in this research (i.e., percentage of scenarios with maximum glance over a threshold) will not improve in six months either.…”
Section: Discussionmentioning
confidence: 98%
“…However, it has been noted that observing road conditions can help drivers gain a comprehensive understanding of the surrounding traffic environment and is essential for safe driving [44,45]. The habit of observing road conditions must be developed through extensive driving experience, and novice teenage drivers may almost focus exclusively on the road ahead [46]. Older and more experienced drivers are observed in cluster 2.…”
Section: Driving Performancementioning
confidence: 99%